Tema 3 picture book form A - Ginsburg, HHerbert páginas; Baroody, Arthur J.
3-0 through 8-11 Testing Time: 40 minutes Administration: Individual The TEMA-3 measures the mathematics performance of children between the ages of 3-0 and 8-11 and is also useful with older children who have learning problems in mathematics. It can be used as a norm-referenced measure or as a diagnostic instrument to determine specific strengths and weaknesses. Thus, the test can be used to measure progress, evaluate programs, screen for readiness, discover the bases for poor school performance in mathematics, identify gifted students, and guide instruction and remediation. The test measures informal and formal (school-taught) concepts and skills in the following domains: numbering skills, number-comparison facility, numeral literacy, mastery of number facts, calculation skills, and understanding of concepts. It has two parallel forms, each containing 72 items. The all new standardization sample is composed of 1,219 children. The characteristics of the sample approximate those in the 2001 U.S. Census. Test results are reported as standard scores, percentile ranks, and age and grade equivalents. Internal consistency reliabilities are all above .92; immediate and delayed alternative form reliabilities are in the .80s and .90s. In addition, many validity studies are described. Also provided is a book of remedial techniques (Assessment Probes and Instructional Activities) for improving skills in the areas assessed by the test. Numerous teaching tasks for skills covered by each TEMA-3 item are included. After giving the test, the examiner decides which items need additional assessment information and uses the book to help the student improve his or her mathematical skills. Several important improvements were made in the TEMA-3. First, a linear equating procedure is used to adjust scores on the two test forms to allow the examiner to use scores on form A and B interchangeably. Second, bias studies are now included that show the absence of bias based on gender and ethnicity. Finally, the pictures of animals and money in the picture book are now in color to make them more appealing and more realistic in appearance. You can use the TEMA-3 in a variety of settings, such as preschools, elementary schools, and clinics. The two forms of the test allow you to study a child's mathematics progress over time.